Design and Validity of Student Worksheet Integrated Scientific Literacy for The Use of Physics Practicum KIT - Hidayati Hidayati; Allin Wel Ningsi; Ananda Mahaputra Iskandar (Jurnal Penelitian Pendidikan IPA, 2023)
The 2013 curriculum contains 4 components, one of which is literacy skills. One of the important literacy skills in learning physics is scientific literacy. Physics learning is always closely related to practicum which requires practicum tools such as the physics practicum KIT. The reality found in the field is the KIT for physics practicum in schools is available but has not been utilized optimally by teachers and the worksheets used have not been integrated with scientific literacy. This study aims to determine the validity value of the student worksheet integrated scientific literacy for the use of physics practicum KIT. The type of research carried out was research and development on Sugiyono's book which consisted of 10 stages, but in this study it was only limited to the design revision stage. The object that is the focus of research is the student worksheets used in schools. The data analysis technique used in this research is descriptive statistics, namely validity analysis. Based on the research, it can be concluded that the validity score of the LKS integrated with scientific literacy for the use of KIT practicum was obtained from an analysis of content eligibility with a value of 0.87; language component with a value of 0.85; clarity component with a value of 0.87 and a graphic component with a value of 0.89. The average validity value of the integrated scientific literacy worksheet for the use of the physics practicum KIT is 0.87 which is classified as very valid.